The Optimization of Micro-Edm Machining Process when Using Carbon Coated Micro Electrode as a Tool - Bich Thi Mac; Shailesh Shirguppikar; Vaibhav Ganachari (Journal of Machine Engineering)
The amount of electrode wear in micro-EDM has a direct effect on the dimensional accuracy of the machined hole. Therefore, improving the corrosion resistance of electrodes in micro-EDM is still of great interest. The effective coating of thin film for the micro tool electrodes in the case of micro-EDM can lead to minimize the electrode wear which eventually improve the productivity and machining quality. In the present study, experiments were performed on micro-EDM using carbon coated tool electrode and optimized using Taguchi-Topsis to investigate optimum levels of Depth of cut (Z) and overcut (OVC). It was concluded that optimum conditions had improved significantly using carbon coated micro tool electrode. Optimal levels of technological parameters include V = 160 V, C = 10000 pF, RPM = 600 rpm, and Zopt = 2.525 mm, OVCopt = 65.257 m. The quality of the machined surface with the coated electrode at optimal conditions is analysed and evaluated. The Topsis method is a suitable solution to this problem, and the steps to perform the calculation in this technique are simple.